Analisis Sistem Pelayanan Bank Darah Rumah Sakit Di Rumah Sakit Daerah Dr. M. Yunus Bengkulu Tahun 2018 - Oktarianita Oktarianita; Wulan Angraini; Henni Febriawati (Avicenna: Jurnal Ilmiah, 2018)
Quality, safe blood services are available on time, can be achieved if the service runs in a closed system, where the hospital no longer submits efforts to obtain transfusion blood to the patient's family, but the entire service mechanism is carried out by the officer. Researchers found that when blood was distributed, the treatment of the blood banks involved families of patients to distribute the blood.This research is a descriptive study with a qualitative approach. Data collection techniques using interviews and observation with a checklist sheet. This research was conducted at Dr.M. Yunus Bengkulu Hospital Blood Bank. The informants in this study were seven people, namely the Head of Hospital Blood Bank, 3 Hospital Blood Bank Staff and three patients' families.The results of this study were the request and receipt of donor blood from UTD in Hospital Blood Bank, blood and blood component storage in Hospital Blood Bank, transfusion blood preparation in Hospital Blood Bank, pre transfusion examination in Hospital Blood Bank, distribution to the treatment room in Hospital Blood Bank, tracing transfusion reactions in Hospital Blood Bank and recording and reporting in Hospital Blood Bank in accordance with Minister of Health regulations No.91 of 2015.Advice given to Hospital Blood Bankâ€™s Officers to meet blood service standards is by distributing closed cold chain systems and in accordance with Minister of Health regulations No.91 of 2015.Â Keywords: System, Service, Blood, Hospital, Bank